Design of an in-ear EEG device to detect consciousness levels and be used in monitoring anaesthesia levels of a patient in a medical setting - Wessels, Carel (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.